Water Pollutant Index (WPI) pada Koridor Hijau Sungai Jawi Pontianak - Jockie Zudhy Fibrianto; Achmad Eko Yanuar Achmad Eko Yanuar; Gusti Rachman Adhiarza Gusti Rachman Adhiarza (Politeknik Negeri Pontianak, 2025)
Abstract: Water Pollutant Index (WPI) is the next indicator to be examined in this study for determining the Environmental Quality Index (EQI) of the green corridor (N. Listyaningrum, 2021). Water pollution is one of the components that must be measured and analyzed to determine whether the water elements within the Sungai Jawi green corridor are polluted or not. According to the Ministry of Environment and Forestry (2019), the Water Pollutant Index (WPI) or Water Quality Index (WQI) can be determined through measured parameters, including Total Suspended Solids (TSS), Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Phosphate, Fecal Coliform, and Total Coliform. The calculation of the Water Quality Index uses the pollution index method, which applies the concept that the higher the pollution index value, the poorer the water quality. This assessment refers to the Class II water quality standards based on Government Regulation Number 82 of 2001. The research methods employed include: 1) Identification, by conducting measurements according to the established parameters; 2) Analysis, by performing calculations using formulas provided by the Ministry of Environment and Forestry; 3) Hypothesis formulation, to obtain results and conclusions regarding the Water Quality Index values of the Sungai Jawi green corridor; and 4) Preparation of the WPI map for the Sungai Jawi green corridor at Gertak sections 1 and 2, based on the results of the formulated hypothesis. The results indicate that the Water Pollutant Index (WPI) or Water Pollution Index of the Sungai Jawi River at Gertak sections 1 and 2 falls under the lightly polluted classification. The WPI (Pij) values obtained were 1.868 at point 1, 1.833 at point 2, and 1.742 at point 3. The lightly polluted classification indicates that one or more measured parameters exceed the established water quality standards, specifically the Class II water quality standard.